(untitled) - Sansom, George (Oxford, 1928)
In the following study of the development of the Japanese language, it has been necessary for reasons of space as well as simplicity to concentrate on a description of the earliest and the lastest forms, those of the Nara and hein periods and of the present day, without paying much attention to the intervening stages.
Keywords: Japanese language; Grammar,Historical